1996
DOI: 10.1113/jphysiol.1996.sp021495
|View full text |Cite
|
Sign up to set email alerts
|

Selective proton permeability and pH regulation of the influenza virus M2 channel expressed in mouse erythroleukaemia cells.

Abstract: 1. The M2 protein of influenza A virus is implicated in transmembrane pH regulation during infection. Whole-cell patch clamp of mouse erythroleukaemia cells expressing the M2 protein in the surface membrane showed a conductance due to M2 which was specifically blocked by the anti-influenza drug rimantadine. 2. The ion selectivity of the rimantadine-sensitive current through M2 was determined.Reversal potentials were close to equilibrium potentials for transmembrane pH gradients and not to those for Na+, K+ or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
348
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(384 citation statements)
references
References 25 publications
(43 reference statements)
28
348
2
Order By: Relevance
“…His37 protonation stabilizes M2 tetramers and also occurs at much higher pH compared with His in free solution (Hu et al, 2006), supporting a 'dimer of dimers' model for the His37 tetrad where each pair shares a single proton (Sharma et al, 2010). This allows one His of each pair to interact with adjacent Trp41, whereupon a third protonation event induces channel opening via alteration of the helical bundle and opening the Trp41 gate (Chizhmakov et al, 1996;Pielak & Chou, 2010). However, alternative models for M2 gating are also proposed, including a 'shuttle' mechanism of proton conductance, whereby exchange of protons between His37 and water residues are facilitated by imidazole ring reorientations (Hong & DeGrado, 2012;Hu et al, 2010;Khurana et al, 2009;Phongphanphanee et al, 2010).…”
Section: Iav M2mentioning
confidence: 96%
See 2 more Smart Citations
“…His37 protonation stabilizes M2 tetramers and also occurs at much higher pH compared with His in free solution (Hu et al, 2006), supporting a 'dimer of dimers' model for the His37 tetrad where each pair shares a single proton (Sharma et al, 2010). This allows one His of each pair to interact with adjacent Trp41, whereupon a third protonation event induces channel opening via alteration of the helical bundle and opening the Trp41 gate (Chizhmakov et al, 1996;Pielak & Chou, 2010). However, alternative models for M2 gating are also proposed, including a 'shuttle' mechanism of proton conductance, whereby exchange of protons between His37 and water residues are facilitated by imidazole ring reorientations (Hong & DeGrado, 2012;Hu et al, 2010;Khurana et al, 2009;Phongphanphanee et al, 2010).…”
Section: Iav M2mentioning
confidence: 96%
“…Slow conductance (*200 H + s 21 ) and a lack of alkali metal ion conductivity pointed to the presence of a selectivity filter, which was highly likely to involve protonation of ionizable residues based upon the induction of activity by reduced external pH (Lin & Schroeder, 2001;Mould et al, 2000). The highly conserved His37 residue within the TMD was shown by mutagenesis to govern M2 selectivity, although His37 mutants retained amantadine sensitivity (Chizhmakov et al, 1996;Wang et al, 1995). Another highly conserved Trp41 'gate' residue combines with His37 to form a now well accepted functional HxxxW tetrad in all M2 proteins, supported by numerous structural and functional studies.…”
Section: Iav M2mentioning
confidence: 99%
See 1 more Smart Citation
“…The binding affinity of each enantiomer results from chiral interactions with the binding area inside the 4-fold symmetric M2 protein. Based on differences in isotropic chemical shift changes measured using ssNMR and MD simulations results, it has been recently suggested that 2-R and 2-S have a strong but differential binding to full length M2, i.e., that 2-R binds more tightly than 2-S. 23 This was the first state of the art ssNMR study of the full M2 protein and analysis of the rimantadine enantiomers binding by ssNMR, but this conclusion appears to be puzzling because: (1) 2-R and 2-S have similar in vivo antiviral activity in protecting mice from lethal influenza; 24 (2) rimantadine was developed prior to the 1992 FDA guidance on the development of stereoisomers. It was approved as commercial drug in the US in 1993 containing both enantiomers.…”
mentioning
confidence: 99%
“…The homotetrameric M2 channel is known to undergo a pH dependent conformational transition that underlies its proton gating and conductance activity. [6][7][8][9][10][11][12][13][14][15][16] The tetrad formed by the His37 residues is believed to play a key role in controlling the transition between the closed and open states, via a protonation/deprotonation mechanism. 10,12,13,[17][18][19][20] At neutral pH the equilibrium distribution of conformers is dominated by the doubly protonated (or +2) state of the His37 tetrad, while at acidic pH the +3 state is also formed.…”
Section: Introductionmentioning
confidence: 99%